BENTUK DIGITALISASI DESA WISATA DI MASA NORMAL BARU STUDI KASUS DESA SAYAN UBUD BALI - I Gede Gian Saputra (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
The digitization of tourism village amidst limited human resource capabilities is a challenge for Sayan Village Ubud Bali. This study aims to analyze the form of digitization of Sayan tourism villages in the new normal era. This study was designed with a qualitative descriptive analysis method followed by a case study approach. In addition to in-depth interviews and focus group discussions, 102 respondents were successfully obtained in distributing questionnaires to support the results that have been carried out. The results of the study reveal that form of digitization seen in the tourism village product marketing. Social media applications such as Facebook, Instagram, Youtube and Google were the digital tools that dominate the form of digitization done by the managers of Sayan Tourism Village. However, Sayan Tourism Villagehave very positive efforts in starting digitization through the collaboration with the Godevi as the marketplace of tourism village.